Gem-diol and Ketone Crystal-to-crystal Transition Phenomena. Issue 1 (December 2017) - Bo, Zhang; Sitong, Chen; Weiming, Guo; Weijing, Zhang; Lin, Wang; Li, Yang; Jianguo, Zhang
Abstract The generally thought unstable diol compound tetrazyl gem-diol (1, H2 DTMdiol·2H2 O), was firstly obtained in crystalline form by culturing the filtrate for ten days after acidification and filtration of aqueous solution of potassium salt of ketone (2, [K(HDTMone)·2H2 O]n ). The stability of this novel gem-diol compound is found owning to the hydrogen bonds with lattice water molecules and electrophilic tetrazolyl groups. Meanwhile, the undissolved ketone (3, H2 DTMone) was separated during the filtration in the process of gem-diol compound production. Surprisingly, the crystal-to-crystal perfect transition phenomena from gem-diol (1) to ketone (3) were firstly observed after heating up to 120 ° C as evidenced by X-ray single crystal diffraction and powder X-ray diffraction. These results found here might open new revenues for methylene oxidation and alkanediol chemistry.